Modeling precipitation kinetics in multicomponent alloys during deformation - Bonvalet Rolland, Manon; Borgenstam, Annika (Frontiers in Materials, 2022)
A new mean-field modeling tool is developed to correctly tackle the problem of precipitation during deformation. The model is an extension of a previously developed Langer–Schwartz–Kampmann–Wagner precipitation modeling approach for multicomponent alloys. The latter is now integrated together with Thermo-Calc software and with physically based equations describing the evolution of the dislocation density during hot-working. New equations for the nucleation barrier and the critical size have also been added to correctly simulate the early stages of precipitation. The model is applied to hot compression tests, for which experimental information was available. The model shows the importance of accounting for the overall precipitation kinetics, and not only for constant values of the precipitate volume fraction or size, to investigate the mechanical property evolution. This is due to a complex interplay between the defects and the precipitates’ evolution driven by a competition between thermodynamics and kinetics. Finally, it is highlighted how the strain rate used affects the final microstructure of the material.